Review article: selective histone deacetylase isoforms as potential therapeutic targets in inflammatory bowel diseases. Issue 1 (4th November 2014) - Felice, C.; Lewis, A.; Armuzzi, A.; Lindsay, J. O.; Silver, A.
Summary Background A link between histone deacetylases (HDACs) and intestinal inflammation has been established. HDAC inhibitors that target gut‐selective inflammatory pathways represent a potential new therapeutic strategy in patients with refractory inflammatory bowel diseases (IBD). Aims To review the use of selective HDAC inhibitors to treat gut inflammation and to highlight potential improvements in selectivity/sensitivity by additional targeting of HDAC‐regulating microRNAs (miRNAs). Methods Original articles and reviews have been identified using PubMed search terms: 'histone deacetylase', 'HDAC inhibitor', 'inflammatory bowel disease', 'gut inflammation, ' and 'microRNA and HDAC'. Results The use of butyrate in distal colitis provided the first evidence that inhibition of HDACs decreases intestinal inflammation in IBD. HDAC inhibitors, such as valproic acid, vorinostat and givinostat, reduce inflammation and tissue damage in experimental murine colitis. Potential mechanisms of action for HDAC inhibitors include increased apoptosis, reduction of pro‐inflammatory cytokine release, regulation of transcription factors and modulation of HDAC‐regulatory miRNAs. HDAC2, HDAC3, HDAC6, HDAC9 and HDAC10 isoforms seem to be specifically involved in chronic intestinal inflammation, justifying the use of selective inhibitors as new therapeutic strategies in IBD. Controlling miRNAs for these isoforms can be identified. Conclusions The pro‐inflammatory influence of HDACs in the gut has been confirmed, but mostly in murine studies. Considerably more human data are required to permit development of selective HDAC inhibitors for IBD treatment. Inhibition of key HDAC isoforms in combination with modulation of HDAC‐regulatory miRNAs has potential as a novel therapeutic approach.